2011
DOI: 10.1111/j.1469-7580.2011.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal development of deep back muscles in the human thoracic region with a focus on transversospinalis muscles and the medial branch of the spinal nerve posterior ramus

Abstract: Fetal development of human deep back muscles has not yet been fully described, possibly because of the difficulty in identifying muscle bundle directions in horizontal sections. Here, we prepared near-frontal sections along the thoracic back skin (eight fetuses) as well as horizontal sections (six fetuses) from 14 mid-term fetuses at 9-15 weeks of gestation. In the deep side of the trapezius and rhomboideus muscles, the CD34-positive thoracolumbar fascia was evident even at 9 weeks. Desmin-reactivity was stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…*Facial nerve muscles: the muscles innervated by the facial nerve were not present in our specimen except for the stylohyoid and posterior belly of digastric muscle. ** Sato et al (2011) did not identify this muscle, but Mekonen et al (2016) did.…”
Section: Upper Limbsmentioning
confidence: 93%
See 1 more Smart Citation
“…*Facial nerve muscles: the muscles innervated by the facial nerve were not present in our specimen except for the stylohyoid and posterior belly of digastric muscle. ** Sato et al (2011) did not identify this muscle, but Mekonen et al (2016) did.…”
Section: Upper Limbsmentioning
confidence: 93%
“…The existence of the spinalis muscle at CS23 is controversial. Based on the observed location, the muscle could not be found in a study assessing 7-to 13-week-old fetuses (Sato et al 2011) but was present at a stage 23 human embryo according to Mekonen et al (2016). In concordance with Mekonen et al (2016), the spinalis muscle was also identified (Fig.…”
Section: Trunkmentioning
confidence: 99%
“…The following have been put forth to be the basis for pain: an osteophyte impinging on a nerve, a capsule being stretched, synovial villi being trapped within articular surfaces, and chemicals that cause an inflammatory reaction (64,66,(68)(69)(70)(71)(72)(73)(74)(75)(76)(77). Facet joints also have been shown to be richly innervated by the medial branches of the dorsal rami (35,70,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91). In addition to this innervation, neuroanatomic, neurophysiologic, and biomechanical studies have shown that facet joints have both free and encapsulated nerve endings and that they also have nerves that contain substance P as well as calcitonin gene-related peptide (CGRP) (62,64,74,75,80,81,.…”
Section: Methodsmentioning
confidence: 99%
“…They are located in the posterior vertebral spine and their function is the keep the torso upright while we are standing or sitting. [17][18][19][20][21][22] There is a close relationship between the paravertebral muscles and low back pain. Studies to evaluate the muscle strength of patients with mechanical low back pain have found severe hypotrophy of the paravertebral musculature of these patients among their results, showing the close relationship between mechanical low back pain and weakness of the paravertebrals.…”
Section: Low Back Painmentioning
confidence: 99%